Transformation of industrial revolution 4.0 in the construction industry: Understanding drivers & barriers with dematel algorithm - Lee, Chia Kuang; Chen, Min Si; Mohd Zainudin, Nurhaizan; Fauzi, M. A.; Toh, Tien Choon (Penerbit Universiti Malaysia Pahang, 2022)
Modern digitalization technology known as Industrial Revolution 4.0 (IR 4.0) has the potential to enhance business operations and communication networks across a variety of sectors. The lack of high-tech processes and technology in the construction industry, however, is growing the distance between the industry and IR 4.0 change. There has not been any prior research on the drivers and challenges of the IR 4.0 transition in the construction industry using DEMATEL. Therefore, the DEMATEL method was utilised to assess the interaction between the drivers and barriers of the IR 4.0 revolution in the construction industry. From the literature review, a list of factors that influence and hinder growth was taken. During interviews, 17 experts provided data using the DEMATEL questionnaire, which was subsequently used for analysis. The impact-relation map diagram showed key elements and their relationships. The outcome demonstrates challenges with the Incompatibility of Innovations (P) is the most significant issue, which is a major barrier that must be overcome. As a result, the listed drivers can be improved further, and the mentioned barriers can be overcome.